Physical simulation experiment on horizontal docking well leaching for salt cavern storage - Jianfu WANG; Zuoliang JIN; Jianguang LI; Jianchao JIA; Kuoyuan ZHU; Zhaoheng ZHOU (You-qi chuyun)
Objective Horizontal docking well leaching is prevalently applied among salt chemical enterprises for brine extraction. However, controlling the cavern shape becomes challenging when this technique is utilized, primarily due to the absence of dissolution inhibitor cushions. Although this cushion method is commonly employed in salt cavern storage to improve cavern shape control, it has not been applied to docking well leaching. To effectively guide the field application of this method, research into the influence patterns of dissolution inhibitor cushions on the cavern shapes resulting from docking well leaching and brine concentrations is necessary. Methods Based on the characteristics and deficiencies of brine extraction methods currently applied by salt enterprises, a novel approach for docking well leaching was introduced. This process involves alternating water injection between two wells equipped with dissolution inhibitor cushions and the phased lifting of tubing strings for leaching and cushions. Based on the similarity theory, an experimental platform was set up for physical simulations of docking well leaching using the proposed approach. The accuracy of the simulation results was verified through a comparison with field data collected from a docking well at Huai'an Salt Mine in Jiangsu Province. Furthermore, this study delved into the influence patterns of various factors on cavern shapes and mass concentrations in brine displacement, including formation dips, displacements, cushion and tubing string control, as well as water injection circulation modes. Results The caverns produced by horizontal docking well leaching optimized by dissolution inhibitor cushions exhibited U-shaped configurations with substantial volumes and high brine concentrations, surpassing those achieved by a single vertical well setup. The presence of formation dips led to elevated horizontal channels and decreased mass concentrations in brine displacement during water injection into the vertical well. Significant displacements contributed to increased cavern volumes, expanded horizontal channels, and enlarged caverns on both sides. Cushion control notably impacted cavern shapes, with prolonged retention at the same position leading to flat tops. Conversely, tubing string control had minimal influence on cavern shapes. Additionally, in the presence of formation dips, the water injection circulation modes notably influenced cavern shapes and mass concentrations in brine displacement. Conclusion The horizontal docking well leaching enhanced by dissolution inhibitor cushions offers an efficient way of leaching, showcasing benefits such as manageable cavern shapes and elevated brine concentrations. This technique stands out as a dominant area for the advancement of leaching methods in salt cavern storage. Nevertheless, given the constraints of laboratory research, future efforts should prioritize conducting field experiments.